TAFSIR AYAT BULLYING: ANALISIS KOMPARATIF KATA HUMAZAH DAN LUMAZAH MENURUT TAFSIR AL-MISBAH, AN-NUR, DAN KEMENAG RI - Rohman, Moch Abdul; Purnomo (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2025)
In general, bullying in the community is familiar, there are many models of swearing carried out on social media that disturb school children and the community, such as what happened at Binus Serpong High School. This makes researchers conduct research related to bullying that occurs on social media, through analysis of the interpretations of Al-Misbah, An-Nur, and KEMENAG RI to contextualize one of the bullying verses contained in surah Al-Humzah. The methodology applied is comparative by determining the theme then analyzing the differences and similarities of the three interpretations. Furthermore, it provides contextualization of humazah and lumazah to answer that bullying is appropriate if understood through a comparative study that juxtaposes the three interpretations. The problem that needs to be sought according to researchers is how is the interpretation given by Quraysh, Hasbi, and the Ministry of Religious Affairs of the Republic of Indonesia? What is the point of difference between the three interpretations? The interpretation of the three mufassir figures emphasizes the tahlili style that is colored with ijtima'I because each of them has different problems. Humazah for Quraysh is permissible in Islam when following one of the six conditions, for example, the purpose of the detractor or blasphemer so that the victim can change his bad nature, this good intention is what Al-Misbah uses as the basis for legalization